Modeling formulas of the comprehensive diagnosis and recommendation system (DRIS) for phosphorus in sugarcane - Pereira da Silva, Gilmara; Prado, Renato de Mello [UNESP]; Wadt, Paulo Guilherme Salvador; Silva, Fabio Cesar da; Vaz, Glauber Jose; Moda, Leandro Rossato [UNESP]; Caione, Gustavo (Taylor & Francis Inc, 2020)
The use of accuracy measures for modeling the formulas of the Comprehensive Diagnosis and Recommendation System (DRIS), can improve the efficiency of the method in assessing the nutritional status in sugarcane. Therefore, the objective was to use the accuracy measures proposed by Wadt and Lemos for the modeling of DRIS formulas in sugarcane, based on the nutritional status for phosphorus. The database was created based on productivity and leaf contents of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn for sugarcane, considered in two agricultural years. (2013 and 2014) making a total of 1,224 samples. DRIS formula modeling was performed using the seven accuracy measures proposed by Wadt and Lemos. The lowest productivity losses were registered using the sensitivity factor f = 2.5 and the productivity response limit of 40% in the 2013 and 2014 harvest. However, there is a need for a greater number of studies to achieve productivity gains when adopt DRIS to assess the nutritional status of sugarcane. The measure of accuracy of nutritional sufficiency at the response limit of 20 and 40% showed a better performance, which can avoid losses in the management of fertilization.
Keywords: accuracy; adjustment fator; Saccharum officinarum